The Effect of Co-Processed Excipient and Mannitol on Physical Properties and Release Test of Flavonoid Total of Bajakah Root (Spatholobus littoralis Hassk.) Water Extract in Effervescent Granule - Dian Eka Ermawati; Nur Cahyo Fajar Trihantono; Ulfa Afrinurfadhilah Darojati; Nindita Claurisa Amaris Susanto; Sholichah Rohmani; M. Fiqri Zulpadly; Annisa Diyan Meitasari; Diyah Tri Utami; Anif Nur Artanti; Heru Sasongko; Meta Kartika Untari (ALCHEMY Jurnal Penelitian Kimia, 2026)
Bajakah root is traditionally used in herbal medicine and exhibits notable antioxidant activity (IC₅₀ = 0.155 mg/mL) with a total flavonoid content of 32.49 ppm. However, conventional consumption by boiling is limited by poor taste, odor, and low stability. To overcome these limitations, this study developed effervescent granules to enhance acceptability and absorption. The effect of combining co-processed excipients (lactose–manihot starch in a ratio of 64.32:35.68) with mannitol on granule characteristics and flavonoid release was investigated. Bajakah root extract was prepared by hot water infusion (90 °C, 15 min; ratios 1:10 and 1:20) followed by freeze-drying. Phytochemical contents were analyzed using UV–Vis spectrophotometry. Co-processed excipients were prepared via wet granulation and characterized by SEM. Formulations with co-processed excipient–mannitol ratios of 3:1, 2:2, and 1:3 were evaluated for physicochemical properties and flavonoid release. Results showed total flavonoid and tannin contents in the extract of 2.19% and 9.04%, respectively. Excipient ratios significantly affected flow rate, angle of repose, moisture content, and disintegration time (p < 0.05), but not pH. All formulations met pharmacopoeial requirements for ≥80% flavonoid release within 60 min. The optimal formulation (1:3) demonstrated excellent properties, supporting its potential as an effective herbal delivery system.